Aging populations threaten conservation goals of zoos - João Pedro Meireles; Max Hahn-Klimroth; Laurie Bingaman Lackey; Nick van Eeuwijk; Mads Frost Bertelsen; Severin Dressen; Paul Wilhelm Dierkes; Andrew J. Abraham; Marcus Clauss (Proceedings of the National Academy of Sciences, 2026)
Improvements in wildlife husbandry mean that many zoo animals are living longer. This has put pressure on the finite holding capacity of zoos, which has often been addressed through a curtailing of reproduction to reduce population growth rates. Here, we explore how such actions have impacted the demographic trends of 774 mammal populations in European and North American zoo populations between 1970 and 2023. Irrespective of whether the data are clustered by region, taxonomic group, conservation status, or breeding program type, the proportion of old individuals has increased continuously, mirrored by a decrease in juveniles and actively reproducing adults. This aging demographic trend compromises the long-term sustainability of zoo populations and thus the ability of zoos to meet ex situ conservation goals. As the observed trends do not show signs of abating, reflection on current zoo population management is required.